La Paz or Sucre? The conflict for the capital status in Bolivia - Ramón Sánchez, Álvaro (REVISTA ELECTRONICA IBEROAMERICANA, 2023)
The confrontation of the capital status between La Paz and Sucre, although little known internationally, was about to prevent the approval of the Constitution of 2009. In this paper, a theoretical review of the geographical and political studies on the capitals of the States is carried out, with a separate section for the typology elaborated from the world-systems approach. Following these works, the Bolivian conflict is analyzed through a review of its history, paying special attention to the period of the Asamblea Constituyente between 2006 and 2009, and then the arguments that support the positions of both candidate cities are presented. Based on the academic literature, the case of Bolivia could be considered that of an asymmetric shared capital, with La Paz predominating. However, in the absence of an undisputed capital, it is an issue that can be reopened at any time. Starting from the Bolivian experience, conclusions are also drawn that may be useful for other countries experiencing a similar situation.